Pengaruh Jam Kerja Perempuan Terhadap Kesejahteraan Ekonomi Rumah Tangga Di Sumatera Barat - Iskho Latifah; Muhammad Irfan (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study examines the role of labor market activities and the household sphere in shaping household economic well-being, particularly through the contribution of women's working hours. Using the 2023 National Socioeconomic Survey (SUSENAS) microdata, this study analyzes the influence of women's working hours on household economic well-being in West Sumatra, measured through household expenditure, using the Ordinary Least Squares (OLS) regression method. The results show that women's working hours have a positive and significant effect on household economic well-being, indicating that increasing women's working time allocation strengthens family economic capacity through additional income. Furthermore, women's individual characteristics and household structure also play a significant role in influencing expenditure levels. These findings confirm that women's labor supply is a key determinant of household well-being and emphasize the importance of gender-responsive employment policies to improve household well-being and economic resilience in West Sumatra.